2019
DOI: 10.3390/en12060968
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Ventilative Cooling Potentials and Building Energy Savings in Various Climatic Zones

Abstract: The introduction of cool outdoor air can help in reducing the energy consumption for cooling during summer. Ventilative cooling potentials (VCPs) have been defined in various ways in the literature to represent potential cooling hours in specified outdoor temperature ranges. However, the energy-saving potential of ventilative cooling can differ between buildings in the same climatic zone depending on the buildings’ thermal characteristics and system operations. In this study, new VCPs are introduced with an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It divides climate zones into five major groups, namely Tropical Climates (A), Dry Climates (B), Mild Temperate Climates (C), Continental Climates (D) and Polar Climates (E) [29,30]. According to the Köppen-Geiger classification scheme, such five major climate groups are subdivided into 31 sub-types [29][30][31][32]…”
Section: Climate Zone Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…It divides climate zones into five major groups, namely Tropical Climates (A), Dry Climates (B), Mild Temperate Climates (C), Continental Climates (D) and Polar Climates (E) [29,30]. According to the Köppen-Geiger classification scheme, such five major climate groups are subdivided into 31 sub-types [29][30][31][32]…”
Section: Climate Zone Classificationmentioning
confidence: 99%
“…In these terms, designing for better energy performance is one of the key issues of sustainable construction [4,48], which involves a holistic approach to energy consumption and emissions to encourage environmental friendliness in buildings [49]. This way of creating buildings that are energy efficient [32,49], appropriately and architecturally designed for their context of use [50] and comfortable for occupation by people [51]. The majority of energy consumption in buildings is caused by heating, cooling and lighting purposes [52].…”
Section: Design Requirements For Sustainable Constructionmentioning
confidence: 99%
“…Several studies have investigated the effect of NV on thermal comfort [22][23][24][25][26][27], of which, Gou et al [22] examined the occupant perception of the thermal environment in naturally ventilated residences in Singapore. The results showed that occupants showed a higher heat tolerance than that outlined by the specifications of the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE).…”
Section: Introductionmentioning
confidence: 99%
“…Energy usage per unit floor area in fully ventilated office buildings can be 10-20 times higher than in residential buildings [19]. Green office buildings have different heating and cooling loads depending on climate zones [20]. Conversely, the transparency of the building envelope has increased since the mid-twentieth century, leading to high energy heating and cooling loads, particularly in green office buildings [21,22].…”
Section: Introductionmentioning
confidence: 99%